2014
DOI: 10.1890/es13-00347.1
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamics in a novel ecosystem: agroforestry effects on grassland vegetation in Uruguay

Abstract: Abstract. Human activities have resulted in novel ecosystems around the globe, but many of these ecosystems are poorly understood, particularly when multiple disturbances interact to create novel combinations of species. The Campos ecoregion of South America is one of the most extensive grasslands globally, yet is unique in the fact that there has been little historical evidence of herbivory or fire that traditionally maintain grassland ecosystems. Livestock were introduced several centuries ago, and afforesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Similar observations were made in Uruguay (Six et al. ) and Australia (Zaloumis and Bond ). Active attempts at native grassland restoration are rare, as for native forest restoration; among other reasons are lack of suitable techniques and commercial seed sources (Overbeck et al.…”
Section: Discussionsupporting
confidence: 87%
“…Similar observations were made in Uruguay (Six et al. ) and Australia (Zaloumis and Bond ). Active attempts at native grassland restoration are rare, as for native forest restoration; among other reasons are lack of suitable techniques and commercial seed sources (Overbeck et al.…”
Section: Discussionsupporting
confidence: 87%
“…Nowadays, Eucalyptus plantations are progressively replacing Pinus. Current afforestation practices may reduce species richness and alter the composition of grassland vegetation in Uruguay [21]. Yet, studies on the impact of Eucalyptus plantations in Uruguay are scarce, and the overall impact of plantations on local ecosystems is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While our research is limited to mid-rotation pine plantations in the Campos, previous research on vegetation dynamics in forest plantations in the Campos ecoregion has reported that species richness declines with forest development from planting until mid-rotation but recovers following thinning and harvest (Six et al 2014), at least during and after the first rotation of plantation forest. Therefore, plant richness response to grazing and afforestation may well vary with forest age.…”
Section: Discussionmentioning
confidence: 99%